Relationship between paraglottic space invasion and cervical lymph node metastasis in patients undergoing supracricoid partial laryngectomy - Joo, Young-Hoon; Park, Jun-Ook; Cho, Kwang-Jae; Kim, Min-Sik (Head & neck, 2012)
Background To investigate the relationship between paraglottic space (PGS) invasion and lymph node metastasis in patients undergoing supracricoid partial laryngectomy. Methods The study included 98 subjects with squamous cell carcinoma of the glottis. Results The PGS invasion rate was 60.2% (59/98), and a significant correlation was found between PGS invasion and cervical lymph node metastasis (p = .022). Fifteen of the 59 patients (25.4%) with PGS invasion, only 3 of the 39 patients (7.7%) without any evidence of PGS invasion had lymph node metastasis. Furthermore, a significant correlation was also found between PGS invasion and T classification (p < .001), vocal cord mobility (p < .001), and subglottic extension (p = .014), and patients with no evidence of PGS invasion possibly had a survival benefit (5‐year disease‐specific survival rate, 84% vs 64%; p = .118). Conclusion This study shows that PGS invasion is significantly related to cervical lymph node metastasis in patients undergoing supracricoid partial laryngectomy. © 2011 Wiley Periodicals, Inc. Head Neck, 2012